Effect of Sulphur and GA3 on the Growth and Yield of Onion - Rashid, MHA (Progressive Agriculture, 2013)
An experiment was conducted at the Horticulture Farm of the Bangladesh Agricultural University, Mymensingh to evaluate the effects of sulphur and GA3 on the growth and yield performance of onion cv. BARI Peaj-1. The experiment included four levels of sulphur viz., 0 (control), 15, 30 and 45 kg/ha and four concentrations of GA3 viz., 0 (control), 50, 75, 100 ppm. The experimental findings revealed that sulphur and GA3 had significant influence on plant height, number of leaves per plant, bulb diameter and length, individual bulb weight, splitted and rotten bulb, bulb dry matter content and bulb yield. The highest bulb yield (13.85 t/ha) was recorded from 30 kg S/ha, while the lowest bulb yield (11.20 t/ha) was obtained from control. Most of the parameters showed increasing trend with the higher concentration of GA3. Application of GA3 @ 100 ppm gave the maximum bulb yield (15.23 t/ha), while the minimum value (10.10 t/ha) was observed from control. Almost all the parameters were significantly influenced by combined treatments of sulphur and GA3 except bulb length of onion. The maximum bulb dry matter content (13.50%) and bulb yield (17.10 t/ha) were produced from the application of sulphur @ 30 kg/ha with 100ppm GA3, while the minimum bulb dry matter content (9.23%) and bulb yield (9.33 t/ha) were recorded from control treatment of sulphur with GA3. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16749 Progress. Agric. 21(1 & 2): 57 - 63, 2010